PROPOSED INNOVATION REFORM MODEL FOR THE MINERAL NITROGEN FERTILIZER INDUSTRY IN CHINA TO REDUCE GREENHOUSE GAS EMISSIONS - Dongjia LI, Rui LIU, Li CHEN, Yu GAO, Xuanyu GU, Yu-hua SHI, Jiahuan LIU, Weifeng ZHANG (Frontiers of Agricultural Science and Engineering, 2023)
<ListItem><ItemContent> ● The carbon footprint of the nitrogen fertilizer chain has decreased significantly over the last decade. </ItemContent></ListItem> <ListItem><ItemContent> ● Different nitrogen fertilizer products have different carbon footprints. </ItemContent></ListItem> <ListItem><ItemContent> ● Structural improvement of N fertilizer products can achieve carbon reduction. </ItemContent></ListItem> Globally, the reduction of excessive N losses and greenhouse gas (GHG) emissions is a central environmental challenge in the 21 century. China has huge associated emissions during both production and land application phases. In addition, 70% of N fertilizer in China is produced and land applied as urea, which has high associated emissions. This study utilized life cycle analysis to compare the carbon emission capacity of different N fertilizers and quantified GHG emissions from different N fertilizer chains within China. This enabled a new innovative reform model to be proposed, which aims to decrease the carbon footprint and increase the net ecosystem carbon budget of China. The results showed that the carbon footprint of the N fertilizer industry was about 229 Tg·yr−1 CO2-eq in 2020. Through changes away from urea through the production and land application of a mix of newly emerging fertilizers, liquid fertilizers and standard fertilizer reductions to 174–182 Tg·yr−1 CO2-eq. Through the upgrading of mineral N fertilizer production technology, the carbon footprint of N fertilizer chain can be reduced by 34.8 Tg·yr−1 CO2-eq. Such reductions would reduce China’s total GHG emissions to 140–147 Tg·yr−1 CO2-eq.